2018
DOI: 10.1002/osp4.294
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of canagliflozin against nonalcoholic fatty liver disease: a prospective cohort study

Abstract: SummaryBackgroundNonalcoholic fatty liver disease (NAFLD) is a common cause of chronic liver disease worldwide and is characterized by insulin resistance, hepatic steatosis and often prediabetes or diabetes. Canagliflozin, a selective sodium glucose cotransporter 2 inhibitor, is a new oral anti‐diabetic drug that reduces hyperglycaemia by promoting urinary glucose excretion. Glycosuria produced by canagliflozin is associated with weight loss, mainly due to reduced fat volume and improve insulin resistance. Red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 30 publications
3
46
0
2
Order By: Relevance
“…This lack of effect in patients receiving ertugliflozin may be due to the patient population enrolled; there was no requirement for liver disease, thereby resulting in low levels of baseline fibrosis. In studies of patients with T2DM and NAFLD [ 33 , 34 ] or biopsy-confirmed NASH [ 35 ] treated with SGLT2 inhibitors, on average, baseline FIB-4 scores (mean values were 1.42 and 2.08 in two studies; median value was 1.75 in another study) were higher than those in the present analysis, suggesting that at least some patients in those studies may fall within fibrosis histology stage 3–4 [ 32 ]. In those studies, improvements in the FIB-4 scores were observed following SGLT2 inhibitor treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This lack of effect in patients receiving ertugliflozin may be due to the patient population enrolled; there was no requirement for liver disease, thereby resulting in low levels of baseline fibrosis. In studies of patients with T2DM and NAFLD [ 33 , 34 ] or biopsy-confirmed NASH [ 35 ] treated with SGLT2 inhibitors, on average, baseline FIB-4 scores (mean values were 1.42 and 2.08 in two studies; median value was 1.75 in another study) were higher than those in the present analysis, suggesting that at least some patients in those studies may fall within fibrosis histology stage 3–4 [ 32 ]. In those studies, improvements in the FIB-4 scores were observed following SGLT2 inhibitor treatment.…”
Section: Discussionmentioning
confidence: 99%
“…63 Studies using Canagliflozin in patients with T2DM and NAFLD showed significant reduction in FIB-4 index values and ferritin levels (a marker of hepatic oxidative stress) suggesting improvement in hepatic fibrosis. 64 In a randomized, double-blind placebo-controlled study, patients with NAFLD and T2DM were randomized to placebo, omega-3, Dapagliflozin, and a combination of both omega-3 and Dapagliflozin. Monotherapy with Dapagliflozin reduced measures of hepatocyte injury and Fibroblast Growth Factor 21 (FGF-21) consistent with a disease-modifying effect on NAFLD.…”
Section: Outcomes Of Studies Designed To Evaluate the Efficacy Of Sglmentioning
confidence: 99%
“…SGLT2 inhibitors, including dapagliflozin, canagliflozin, empagliflozin, ipragliflozin, and luseogliflozin are being used increasingly in the treatment of T2DM; they promote weight loss which is an attractive property for the treatment of patients with NAFLD. Although SGLT2 inhibitors are not yet generally recommended for the treatment of NAFLD in patients with T2DM, emerging data suggest that SGLT2 inhibitors reduce the risk of progression of NAFLD [ 112 ], as the following results have been reported: a decrease in hepatic fat content [ 113 114 ]; a decrease in AST and ALT [ 114 115 ]; a decrease in the measures of fibrosis, such as the FIB-4 index [ 115 116 ], the fibrosis index calculated from hyaluronic acid and type IV collagen 7S [ 116 ], and VCTE-measured LSM [ 117 ]; an improvement in hepatic insulin sensitivity [ 114 ]; and histology [ 118 ]. Well-designed RCTs are needed to elucidate whether SGLT2 inhibitors should be used as the first-line drug choice in patients with NAFLD/NASH with T2DM.…”
Section: Treatment Of Nafldmentioning
confidence: 99%